Early debridement with physiotherapy for prevention of postburn contracture of neck: a case series - Bakhshi, Girish D.; Marathe, Aditya B.; Kamat, Chirag; Hussain, Khadeija (International Surgery Journal, 2020)
Hypertrophic scars and contractures are well known sequelae after burns. They result in high morbidity in severely burned patients who are surviving. Present case study was done to establish the usefulness of early debridement and physiotherapy in preventing these sequelae. Present study was conducted on patients admitted in a tertiary care hospital on patients with alleged history of thermal burns to neck and upper chest over a period of 6 months. These patients were subjected to early debridement, daily dressings and early neck physiotherapy. They were assessed for neck mobility and development of neck contracture. Three patients were studied, two had a favourable outcome due to adherence to above measures while one developed contracture due to her late presentation and non-compliance to early physiotherapy. Post burn contractures are common sequelae of thermal burns involving the neck region. Early Debridement, daily dressing of the raw areas with starting of early neck physiotherapy are important and prove beneficial in preventing neck contractures with early return to normal daily activity.